Gambaran Penerapan Rekam Medis Elektronik di Klinik Pratama Polres Pelabuhan Tanjung Priok Tahun 2024 - Dinda Puspita Rahardjo; Anggun Nabila (Jurnal Ilmiah Kedokteran dan Kesehatan, 2026)
The rapid advancement of digital health technologies has necessitated the integration of Electronic Medical Records (EMR) into clinical services to improve efficiency, accuracy, and quality of care. The Primary Clinic of Polres Pelabuhan Tanjung Priok began implementing its EMR sistem (eClinic) on January 1, 2024, in alignment with the Ministry of Health Regulation No. 24 of 2022 regarding digital medical records. A qualitative descriptive approach was applied through a 22-day field internship involving direct observation, interviews with health personnel, and data analysis related to EMR usage. The study observed patient registration, SOAP documentation by doctors, pharmacy services, and monthly drug inventory reporting. The EMR sistem significantly improved patient service efficiency by reducing average waiting times from approximately 60 minutes to 10–15 minutes. The clinic's infrastructure and trained health personnel supported a smooth transition from manual to digital sistems. Additionally, the EMR sistem is integrated with national health platforms such as SATUSEHAT, PCare BPJS, and i-Care JKN, enabling seamless data synchronization and continuity of care. The successful implementation of EMR at the Primary Clinic of Polres Pelabuhan Tanjung Priok demonstrates the importance of digital transformation in enhancing healthcare services. With improved data accessibility, reduced waiting times, and increased patient satisfaction, EMR has become an essential tool in supporting effective clinical workflows and public health service delivery.